2016
DOI: 10.1007/s40572-016-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Interplay Between Social Determinants and Environmental Exposures for Early-Life Outcomes

Abstract: Forty-one studies met the search criteria and were reviewed. Of these, 37, 34, and 29 % of studies focused on asthma, cognition/behavior, and perinatal outcomes, respectively. No study focused on obesity. Across all studies reviewed, 72 % observed significant synergistic associations between social and environmental exposures. Air pollution was the most frequently studied environmental exposure, and socioeconomic status was the most commonly studied social factor. The emerging evidence suggests that social and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 78 publications
4
37
1
Order By: Relevance
“…The potential long-term effects of in utero exposure to DDT/E in low- and middle-income settings where IRS is practiced, including their interaction with maternal and familial factors, such as socioeconomic status ( Appleton et al. 2016 ; Stein et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential long-term effects of in utero exposure to DDT/E in low- and middle-income settings where IRS is practiced, including their interaction with maternal and familial factors, such as socioeconomic status ( Appleton et al. 2016 ; Stein et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our study area (Limpopo Province, South Africa), intestinal infections, influenza, and pneumonia together account for 26.2% and 23.6% of all deaths among infants under 1 y and children 1–14 y of age, respectively ( Statistics South Africa 2017 ). Moreover, early adversity factors such as poverty ( Appleton et al. 2016 ; Stein et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since SES is both related to air pollutants17 and adverse perinatal outcomes,40 socioeconomic characteristics can act as confounders when studying the effects of air pollutants on pregnancy outcomes 41. This potential for bias likely increases with the size of the study area, since large areas are generally more socially diverse; studies in large areas allow considering a large sample size and increasing exposure contrasts, but are also more likely to suffer from confounding by SES and behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to air pollution can have longer-term health effects resulting in mortality [29]. Studies have shown significant associations between exposure to particulate matter and respiratory morbidity among children [30][31][32]. A recent study indicated a biological linkage between air pollution exposure and diarrhea [2].…”
Section: Introductionmentioning
confidence: 99%